Indonesia's contested domains: deforestation, rehabilitation and conservation-with-development in Central Kalimantan's tropical peatlands - Jewitt, Sarah; Nasir, D.; Page, S.E.; Rieley, J.O.; Khanal, K. (Commonwealth Forestry Association, 2014)
Tropical peat swamp forests (TPSF) in Indonesia have long faced competition between industrial demand for timber, the subsistence require- ments of local communities and, more recently, global concern about the need to conserve tropical peat carbon stores, ecosystem services and biodiversity. This paper uses concepts of ecological distribution and environmental justice to investigate how tensions between conservation and livelihood goals have played out on the ground and examine who has gained and lost out from recent TPSF exploitation, conservation and rehabilitation initiatives. A central focus is how peat-based communities in Central Kalimantan have adapted their livelihoods to changing peatland conditions and management policies with particular emphasis on the livelihood impacts of conservation-with-development initiatives in the area. It is argued that despite recent emphasis on ‘win-win’ initiatives, the costs of environmental conservation are rarely distributed in proportion to their benefit.